Pyrolysis of high ash sewage sludge: Kinetics and thermodynamic analysis using Coats-Redfern method - Naqvi, S.R. (2019)
This study aims to investigate the thermo-kinetics of high-ash sewage sludge using thermogravimetric analysis. Sewage sludge was dried, pulverized and heated non-isothermally from 25 to 800 Â°C at different heating rates (5, 10 and 20 Â°C/min) in N2 atmosphere. TG and DTG results indicate that the sewage sludge pyrolysis may be divided into three stages. Coats-Redfern integral method was applied in the 2nd and 3rd stage to estimate the activation energy and pre-exponential factor from mass loss data using five major reaction mechanisms. The low-temperature stable components (LTSC) of the sewage sludge degraded in the temperature regime of 250â450 Â°C while high-temperature stable components (HTSC) decomposed in the temperature range of 450â700 Â°C. According to the results, first-order reaction model (F1) showed higher Ea with better R2 for all heating rates. D3, N1, and S1 produced higher Ea at higher heating rates for LTSC pyrolysis and lower Ea with the increase of heating rates for HTSC pyrolysis. All models showed positive ÎH except F1.5. Among all models, Diffusion (D1, D2, D3) and phase interfacial models (S1, S2) showed higher ÎG as compared to reaction, nucleation, and power-law models in section I and section II. Â© 2018 Elsevier Ltd